Enhancing Hospitality Students' Oral Communication Skills through Vlogging and Peer Feedback - Medrano Loreto, Myla (ASEAN Journal of Education, 2024)
This study aimed to 1) investigate the effectiveness of vlogging as an instructional strategy to improve hospitality students’ oral communication skills and 2) explore students’ perceptions of exchanging peer feedback in their vlogging assignments. A one-group pretest-posttest design was employed. A four-point scale presentation rubric and a reflection guide were the main research instruments utilized in this study. The 42 participants, enrolled in the Principles of Communication class in the first semester of the academic year 2021, produced four vlogs shared in a private Facebook group where they were assigned to exchange peer feedback. The first and last vlogs were assessed using the four-point scale presentation rubric. Paired samples t-tests yielded significant differences in the scores in nonverbal communication, verbal communication, and organization of content. Overall, the students registered the highest improvement in the organization of content. The most substantial improvements in the oral communication subskills were in the areas of purpose, enthusiasm, and composure. Analysis of the student’s reflection papers revealed that the majority perceived the exchange of peer feedback as motivating, useful, and reflective, although reliability and students’ attitudes were viewed as limitations. Vlogging can effectively address gaps in the hospitality students’ lack of confidence, insufficient opportunities for practice, and lack of motivation and active participation in the improvement of their oral communication skills. It facilitates cooperative learning and learning through modeling and observation. The integration of vlogging as an instructional strategy to narrow gaps in other communication skills relevant to hospitality education is proposed.